The Role of Artificial Intelligeence in Supporting Commercial Companies Governance - NASR, HAMADA MOHAMED ABDELATI; Emam, Maher Ibrahim Ebed; Ahmed , Mohamed Elaalim Adam; Alshamrani, Ali Saeed (Journal of Ecohumanism, 2024)
This study aims to address the role of artificial intelligence in supporting the governance of commercial companies, through descriptive and comparative analytical approach.The importance of the study was that governance is one of the most important mechanisms for improving companies’ performance and ensuring the integrity and transparency of their transactions, adopting artificial intelligence to support corporate governance is considered one of the most important features of good governance.The researcher addressed this study through two sections, The first section is devoted to the nature of governance and artificial intelligence and the position of countries on artificial intelligence, The second section discusses the adoption of artificial intelligence as one of the governance mechanisms for commercial companies.At the end of the study, the researcher reached some results and recommendations, the most important of which is that the Egyptian legislator should provide special legislation for artificial intelligence, The legislator should establish specialized courts in artificial intelligence cases, A special guarantee fund should be established to compensate for damages arising from artificial intelligence applications.